2014
DOI: 10.1038/mt.2014.87
|View full text |Cite
|
Sign up to set email alerts
|

Dual-regulated Lentiviral Vector for Gene Therapy of X-linked Chronic Granulomatosis

Abstract: Regulated transgene expression may improve the safety and efficacy of hematopoietic stem cell (HSC) gene therapy. Clinical trials for X-linked chronic granulomatous disease (X-CGD) employing gammaretroviral vectors were limited by insertional oncogenesis or lack of persistent engraftment. Our novel strategy, based on regulated lentiviral vectors (LV), targets gp91(phox) expression to the differentiated myeloid compartment while sparing HSC, to reduce the risk of genotoxicity and potential perturbation of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 45 publications
(67 reference statements)
5
74
0
Order By: Relevance
“…34 Our study included a wide distribution of VCN (ranging from 0.3 to 9.8). While these VCNs are in line with previous studies from our group and others [36][37][38] it is expected that lower VCNs would be observed in the clinical application based on our previous studies in human CD34+ cells, 23 and clinical trials in other therapeutic areas. 34,39 Unfortunately, no published data is available regarding the protection from the infections in clinical trials with lentiviral vectors encoding for gp91phox.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…34 Our study included a wide distribution of VCN (ranging from 0.3 to 9.8). While these VCNs are in line with previous studies from our group and others [36][37][38] it is expected that lower VCNs would be observed in the clinical application based on our previous studies in human CD34+ cells, 23 and clinical trials in other therapeutic areas. 34,39 Unfortunately, no published data is available regarding the protection from the infections in clinical trials with lentiviral vectors encoding for gp91phox.…”
Section: Discussionsupporting
confidence: 91%
“…45 Finally, our data further validate the use of regulated vectors based on transcriptional or post-transcriptional regulators that allow the adequate expression of a functional transgene while preventing ectopic expression in undifferentiated HSCs. 23 Taken together, our results provide a useful and manageable model that mimics the hallmarks of human disease and demonstrates robust preclinical evidence of efficacy and supports the progression to the clinical settings of gene therapy with regulated lentiviral vectors.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations